Urban Heat Island phenomenon and the role of urban green spaces in regulating thermal comfort in Bogor City, Indonesia - Deviro, Sonya Okta; Karlinasari, Lina; Nurhayati, Ati Dwi (Journal of Degraded and Mining Lands Management, 2025)
This study examined the intensification of the Urban Heat Island (UHI) phenomenon in Bogor City, Indonesia, over a ten-year period from 2013 to 2023. Rapid urbanization has led to extensive changes in land cover, primarily the conversion of vegetated areas into built-up zones. This research integrated remote sensing analysis using Landsat 8 OLI/TIRS imagery with field-based measurements of the Temperature Humidity Index (THI) to assess spatial patterns of Land Surface Temperature (LST), vegetation cover (NDVI), and built-up area expansion (NDBI). The results indicated a notable increase in UHI intensity, as reflected in the expansion of high LST zones (29-32 °C) and a reduction in cooler zones (23-26 °C). Built-up areas increased most significantly in Tanah Sareal (11.98%) and West Bogor (8.49%), while vegetation cover declined sharply, especially in North and Central Bogor. Regression analysis showed a strong negative correlation between NDVI and LST (R² = 0.59) and a positive correlation between NDBI and LST (R² = 0.60), confirming the thermal buffering role of vegetation and the heat-amplifying effect of built surfaces. THI measurements indicate widespread thermal discomfort (THI >27 °C) in densely populated urban areas. However, Central Bogor maintains lower LST and THI values, indicating better thermal comfort. These findings highlight the crucial role of urban green infrastructure in mitigating urban heat island (UHI) effects, underscoring the importance of adopting nature-based solutions, such as expanding green spaces and implementing sustainable land management practices, to enhance urban climate resilience.